MODERN INFORMATION ON THE ETIOLOGY OF NECROTIZING FASCIITIS - Korikhonov, D.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Necrotizing fasciitis is an infectious disease of fascial structures, the origin of which is associated with the penetration of an infectious agent into the circulating blood (infection of circulating blood) through damaged skin. The source of infection can be abrasions, abrasions, wounds, including operating ones, including laparoscopy, burns, as well as purulent diseases of various organs. The mechanism of interaction of the microbial factor initiating necrotizing fasciitis with the macroorganism is fundamentally different from the pathogenesis of banal infectious diseases of soft tissues. The purpose of this article is to characterize the microbiota of necrotizing fasciitis based on data from various publications and analysis of our observations.